Enhanced Omicron Variant Neutralization by a Human Antibody Tailored to Wild-Type and Delta-Variant SARS-CoV-2 RBDs - Lee, Jisun; Kim, Bomi; Woo, Hye Min; Kim, Jun Won; Jung, Inji; Park, Seong Wook; Kim, Yong Sung; Na, Jung Hyun; Jung, Sang Taek (Molecular Pharmaceutics, 2024)
Given the previous SARS-CoV-2 pandemic and the inherent unpredictability of viral antigenic drift and shift, preemptive development of diverse neutralizing antibodies targeting a broad spectrum of epitopes is essential to ensure immediate therapeutic and prophylactic interventions during emerging outbreaks. In this study, we present a monoclonal antibody engineered for cross-reactivity to both wild-type and Delta RBDs, which, surprisingly, demonstrates enhanced neutralizing activity against the Omicron variant despite a significant number of mutations. Using an Escherichia coli inner membrane display of a human naïve antibody library, we identified antibodies specific to the wild-type SARS-CoV-2 receptor binding domain (RBD). Subsequent directed evolution via yeast surface display yielded JS18.1, an antibody with high binding affinity for both the Delta and Kappa RBDs, as well as enhanced binding to other RBDs (wild-type, Alpha, Beta, Gamma, Kappa, and Mu). Notably, JS18.1 (engineered for wild-type and Delta RBDs) exhibits enhanced neutralizing capability against the Omicron variant and binds to RBDs noncompetitively with ACE2, distinguishing it from other previously reported antibodies. This underscores the potential of pre-existing antibodies to neutralize emerging SARS-CoV-2 strains and offers insights into strategies to combat emerging viruses.
Keywords: Antibodies, Monoclonal; Antibodies, Neutralizing; Antibodies, Viral; COVID-19; Cross Reactions; Epitopes; Humans; Mutation; Neutralization Tests; Protein Domains; SARS-CoV-2; SARS-CoV-2 variants; Spike Glycoprotein, Coronavirus; antibody; neutralization; noncompetitive interaction; omicron; SARS-CoV-2